Zika detection: comparison of methodologies - Colombo, Tatiana Elias; Bernardes Terzian, Ana Carolina; Araujo Junior, Joao Pessoa [UNESP]; Parreira, Ricardo; Sotello Cabrer, Eliana Marcia; Penha dos Santos, Izalco Nuremberg; Negri Reis, Andreia Francesli; Costa, Fabiana Rodrigues; Arao Antonio Cruz, Lilian Elisa; Rombola, Patricia Lopes; Nogueira, Mauricio Lacerda (Soc Brasileira Microbiologia, 2018)
Many countries in the Americas have detected local transmission of multiple arboviruses that cause febrile illnesses. Therefore, laboratory testing has become an important tool for confirming the etiology of these diseases. The present study aimed to compare the sensitivity and specificity of three different Zika virus detection assays. One hundred serum samples from patients presenting with acute febrile symptoms were tested using a previously reported TaqMan (R) RT-qPCR assay. We used a SYBR (R) Green RT-qPCR and a conventional PCR methodologies to compare the results. Of the samples that were determined to be negative by the TaqMan (R) RT-qPCR assay, 100% (Kappa = 0.670) were also found to be negative by SYBR (R) Green RT-qPCR based on Tm comparison; however, 14% (Kappa = 0.035) were found to be positive by conventional PCR followed by agarose gel electrophoresis. The differences between the ZIKV strains circulating worldwide and the low viremia period can compromise diagnostic accuracy and thereby the accuracy of outbreak data. Therefore, improved assays are required to improve the diagnosis and surveillance of arbovirus. (C) 2017 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda.
Keywords: Zika virus; Detection; Sensitivity; Specificity